1979
DOI: 10.1007/bf01386710
|View full text |Cite
|
Sign up to set email alerts
|

Growth of microorganisms on insoluble polymers: Transformation of automobile tires

Abstract: Microorganisms were isolated that transform 35-mesh automobile tire carcasses, utilizing water-soluble oils in the tire particle as a carbon source, while concomitantly oxidizing the styrene-butadiene copolymer of the insoluble substrate by co-metabolism. The product behaved as a cationic exchanger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Although it is not certain that optimal environmental conditions (particularly pH) for A. ferrooxidans were achieved in our experiments or in the actual monofills, our findings do not support a role for this organism in exothermic reactions associated with tyre shreds. Tyre material contains a variety of organic compounds, such as natural rubber, synthetic rubber and aromatic oils (including polycyclic aromatic hydrocarbons) that can be utilized by certain species of bacteria found in soil and water (Heisey and Papadatos 1995) and by fungi found in soil (Faber and Nickerson 1979). The majority of previously identified rubber degrading bacteria are Actinobacteria, such as Streptomyces sp., Nocardia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not certain that optimal environmental conditions (particularly pH) for A. ferrooxidans were achieved in our experiments or in the actual monofills, our findings do not support a role for this organism in exothermic reactions associated with tyre shreds. Tyre material contains a variety of organic compounds, such as natural rubber, synthetic rubber and aromatic oils (including polycyclic aromatic hydrocarbons) that can be utilized by certain species of bacteria found in soil and water (Heisey and Papadatos 1995) and by fungi found in soil (Faber and Nickerson 1979). The majority of previously identified rubber degrading bacteria are Actinobacteria, such as Streptomyces sp., Nocardia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Tyre material contains a variety of organic compounds, such as natural rubber, synthetic rubber and aromatic oils (including polycyclic aromatic hydrocarbons) that can be utilized by certain species of bacteria found in soil and water (Heisey and Papadatos 1995) and by fungi found in soil (Faber and Nickerson 1979). The majority of previously identified rubber degrading bacteria are Actinobacteria, such as Streptomyces sp., Nocardia sp.…”
Section: Discussionmentioning
confidence: 99%
“…A review of mineral oils in general (covering oils made from dewaxed paraffin‐based crude oils) found their biodegradability to range between 15% and 35% (Aluyor & Ori‐Jesu, 2009), thus slightly above what was observed in the present study. One study found indirect evidence that biodegradation of tire polymers occurs by a cometabolic pathway, which is dependent on the presence of a metabolizable carbon source (Faber & Nickerson, 1979). In addition to being slightly biodegradable itself, the presence of oils (although their bioavailability is likely limited) may thus increase biodegradability of rubber when present in TPs, compared to rubber by itself, by facilitating polymer biodegradation through a cometabolic pathway.…”
Section: Discussionmentioning
confidence: 99%